The Impact of Minimum Wage Increase, Unemployment Rate, and Manufacturing Sector Investment on Workers' Welfare in Indonesia - Judijanto, Loso; Prihanto, Purwaka Hari; Bunyamin, Ilham Akbar (West Science Social and Humanities Studies, 2025)
This study investigates the impact of Minimum Wage Increases (MWI), Unemployment Rates (UNR), and Manufacturing Sector Investment (MSI) on Workers' Welfare (WWF) in Indonesia. A quantitative research approach was used, with data collected from 200 participants, analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) 3. The results indicate that Manufacturing Sector Investment has a significant positive impact on Workers' Welfare, suggesting that industrial investment fosters job creation and better working conditions. Minimum Wage Increase also positively influences Workers' Welfare, improving workers' income and standard of living. Furthermore, Unemployment Rate has the strongest negative effect on Workers' Welfare, highlighting the importance of reducing unemployment to improve workers' well-being. The study suggests that policies promoting manufacturing sector investment, carefully calibrated minimum wage increases, and targeted initiatives to reduce unemployment are essential for enhancing workers' welfare in Indonesia.